Educação ambiental e construção civil: práticas de gestão de resíduos em Foz do Iguaçu-PR - Frigo, Juliana Pires (2012)
Nowadays, one of the biggest worries in a world level is about to preserve the environment,among them, the urban waste production. The wastes have a great relationship with the humanhistory, because they were always present in the daily people lives, so with the constanturbanization process it led the civil building indexes growth, such demands for new building spacesbrought also new environmental problems to the urban centers such as, for example, the finaldestination of the civil buildings wastes or even their proper uses. The present study aims mainlypurpose to promote the awareness of the environmental education importance about the wastesproduced by the civil building. For this, it was used the following methodological procedures:photographic survey where it was possible to identify the mainly civil building wastes destinationsand, the technical leaflet making that characterizes an education practice related to the environment, being dialectic and applied that combine scientific and theoretical, resulting in theapplication and explanation of the subject through the brochure fifteen works in the city of Foz doIguaçu, PR, succeeding in its application, being showed to an adequate language and with an easycomprehension in the aspects that refer to the environmental questions, enabling a totalcomprehension by the professionals and the general population. This practice as an educationform has a fundamental role, because it’s possible to contribute to the individual’s sensitization aswell as in the everyday practices transformation, emphasizing that these information can’t bepassed away as a simple knowledge transference, it is necessary to establish a dialogue, acommunication.